Taxonomic notes on Camellia crassicolumna and its related species (Theaceae) - Jiang, Yin-Zi; Yu, Xiang-Qin; Zhang, Tao; Peng, Hua; Yang, Shi-Xiong (Phytotaxa, 2023)
Camellia crassicolumna (Theaceae) was described as an endemic species to southeastern Yunnan, China. In the most recent monograph of Camellia, seven names, including C. crispula, C. atrothea, C. makuanica, C. haaniensis, C. purpurea, C. rotundata, and C. crassicolumna var. shangbaensis, were listed as heterotypic synonyms of C. crassicolumna. Our examination of related specimens reveals that the statement ‘ovariis pilosis’ in the protologue of C. crassicolumna is incongruent with its type specimens whose ovaries are glabrous. The morphological traits of C. crassicolumna resemble C. kwangsiensis var. kwangnanica. Therefore, C. crassicolumna is reduced into C. kwangsiensis var. kwangnanica. The species status of C. crispula is reinstated with C. atrothea, C. makuanica, C. haaniensis, C. purpurea, C. rotundata, and C. crassicolumna var. shangbaensis treated as its heterotypic synonyms. A new combination, C. crispula var. multiplex, is proposed, and the lectotype of C. atrothea is designated here.